Southern Ocean circulation’s impact on atmospheric CO2 concentration - Laurie Menviel; Laurie Menviel; Paul Spence; Paul Spence (Frontiers in Marine Science, 2024)
In the context of past and present climate change, the Southern Ocean (SO) has been identified as a crucial region modulating the concentration of atmospheric CO2. The sustained upwelling of carbon-rich deep waters and inefficient nutrient utilization at the surface of the SO leads to an outgassing of natural CO2, while anthropogenic CO2 is entrained to depth during the formation of Antarctic Bottom water (AABW), Antarctic intermediate water (AAIW) and sub-Antarctic mode water (SAMW). Changes to the SO circulation resulting from both dynamic and buoyancy forcing can alter the rate of upwelling as well as formation and subsequent transport of AABW, AAIW and SAMW, thus impacting the air-sea CO2 exchange in the SO. Models of all complexity robustly show that stronger southern hemispheric (SH) westerlies enhance SO upwelling, thus leading to stronger natural CO2 outgassing, with a sensitivity of 0.13 GtC/yr for a 10% increase in SH westerly windstress. While the impact of changes in the position of the SH westerly winds was previously unclear, recent simulations with high-resolution ocean/sea-ice/carbon cycle models show that a poleward shift of the SH westerlies also enhances natural CO2 outgassing with a sensitivity of 0.08GtC/yr for a 5° poleward shift. While enhanced AABW transport reduces deep ocean natural DIC concentration and increases surface natural DIC concentration, it acts on a multi-decadal timescale. Future work should better constrain both the natural and anthropogenic carbon cycle response to changes in AABW and the compound impacts of dynamic and buoyancy changes on the SO marine carbon cycle.